The drama of Spain, 1931-1936 : from the proclamation of the Republic to the Civil War 1931-1936 - Ramos Oliveira, A. (Antonio). 1907- (National Council of Labour, 1936)
1936 018a-0006-004 292/946/18a/6(iv)